Isolation of biologically active metabolites from Bougainvillea spectabilis Willd. cultivated in Egypt - Kadriya S. El Deeb; Hanaa H. Eid; Amany A. Sleem; Ghada Farouk Metwally; Menna B. Abdel Halim (International Journal of Phytomedicine, 2020)
Bougainvillea spectabilis Willd. is an ornamental plant cultivated in tropical, subtropical regions and other places as Egypt. The present study aimed to perform bioassay guided fractionation and isolation of some of the bioactive compounds from the Egyptian cultivate. The total ethanol extracts of the leaves (T.ET.L.), stems (T.ET.S.) and flowers (T.ET.F.) were screened for some pharmacological activities viz. in vivo anti-oxidant and anti-hepatotoxic, in addition to in vitro cytotoxic activities. The anti-oxidant effect was assessed by measuring serum glutathione level (GSH) in alloxan-induced diabetic rats. The anti-hepatotoxic activity was evaluated via measuring serum markers level viz. alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP) in CCl4-induced hepatotoxicity in rats. In vitro cytotoxicity of the different extracts was estimated for liver cancer cell line (HEPG2) adopting Sulforhodamine B stain assay. T.ET.L. exhibited significantly potent anti-oxidant and anti-hepatotoxic activities, while T.ET.S. showed the highest cytotoxic activity. Through biological guided fractionation, leaves and stems were subjected to successive solvent extraction, whereas the leaves ethyl acetate (Et.Ac.L.) and the stems ethanol 70% (Et.70%S.) extracts showed highly potent activities. Thus, different chromatographic techniques were performed on Et.Ac.L. and Et.70%S. extracts leading to the isolation of five bioactive metabolites. Three flavonoids were isolated from Et.Ac.L.; genistein-7-O-rutinoside (1), formononetin-7-O-rutinoside (2) and myricetin (3), while orobol-7-O-glucoside (4) and hesperidin (5) were isolated from Et.70%S. This work demonstrated the importance of the plant as a promising anti-oxidant, anti-hepatotoxic and cytotoxic product for nutraceutical use.